(untitled) (Singaporean Journal of Business Economics and Management, 2021)
The purpose of this study is to examine the relationship between religious beliefs, brand personality, and NRCPA, which is New Religious-Complaint Product Adoption. This research-based study is majorly quantitative and conducted through a questionnaire based on a 5-type Likert scale and face to face interviews with the consumers of Fast-Moving consumer goods (FMCG). Results confirm the relationships among all the variables and the extent to which religious consumers tend to behave in accordance to society and Religion. Moreover, this study clarifies how the adoption or favour/disfavour of a new religious product is strongly influenced by religious beliefs, brand personality, and marketing techniques (NRCPA). It is also noted that many relationships be it social or religious are quite often based on certain lifestyles and behaviors of the consumers, consuming the product. The manufacturers take the opinions and thoughts of many individuals before making anything that may be sensitive or promotional to certain religious beliefs. Business associations are set up with the point of making a benefit. The essential goal of any business is to boost returns, and all endeavors are coordinated towards this point. Firms make a benefit by offering products and ventures to the clients. In this manner, high deals volume would mean exceptional yields for an organization. The measure of products and ventures sold by an organization relies upon the interest. At the point when the interest in items is high, there is an expansion in the deals, and this means financial development. This infers there is an immediate connection between how individuals devour items and economy. It is important that customer conduct is a critical determinant of interest. Be that as it may, customer conduct is impacted by Religion as it influences individuals’ qualities and activities. It influences how and when buyers go through their money. This paper examines how religion impacts purchaser conduct and the related effect on the economy